Splay-bend nematic phases of bent colloidal silica rods induced by polydispersity - Ramakrishna Kotni; Albert Grau-Carbonell; Massimiliano Chiappini; Marjolein Dijkstra; Alfons van Blaaderen (Nature Communications, 2022)
Different shapes of molecules or particles can exhibit various liquid crystal phases. The authors report on an experimental discovery of a so called splay-bend nematic liquid crystal phase in a colloidal system of bent silica rods.